"As crianças querem saber como é que se vive!" : a formação de professoras/es de educação infantil em sexualidade e gênero - Blankenheim, Thaís (2021)
This thesis constitutes a work of exploration, approximation and intervention in the fields of sexuality and gender in Early Childhood Education. Starting from the motivation of enabling, from early childhood, that teachers and educators be trained to act as driving the integral development of children, from the contact with knowledge about sexuality and gender and, consequently, from the possibility of intervening in a protective and equitable manner. For this, we had as objectives: 1) To investigate how the themes of sexuality and gender are treated in the Brazilian educational context, more specifically in Early Childhood Education, 2) To identify how these professionals are trained in the fields of sexuality and gender and, therefore, to verify how they are trained for the understanding and management of situations related to the subject, and 3) To build, apply and evaluate a formative intervention in Sexuality and Gender Education for early childhood education professionals. As results, we obtained the development of four articles. The first, "Educational interventions in the field of sexuality and gender in Brazil: a scope review", had as main result the evidence of the lack of studies that focus on the child age group, compared to adolescence, and the minority of studies working with teachers and educators. The second and third articles, respectively, "The (in)visibility of sexuality and gender fields in early childhood education: focus group analysis with educators", and "The school of Early Childhood Education towards sexuality and gender education: exploring the motivations of professionals from Rio Grande do Sul" pointed out gaps, such as the lack of the subject in the training offered by the teaching and pedagogy courses, the insecurity of the teachers/es in the management of the theme, doubts about the development of sexuality in childhood and about gender characteristics (male and female attributions) and orientation/sexual desire. The projected intervention was applied and presented in the fourth article, "Formative intervention in sexuality and gender for teachers/es of Early Childhood Education", which proved to be effective, as it significantly reduced the level of prejudice against sexual and gender diversity of the participants. In addition, an immediate effect was verified in relation to the application of knowledge and the motivation to learn more about the subject. However, not all items have changed significantly and, therefore, it was suggested the development of new interventions that emphasize more subtle manifestations of prejudice related to attitudes about sexual diversity and gender roles.In response to the three general objectives of this thesis, through the four studies conducted, deficiencies were identified in relation to the treatment of the theme in the Brazilian educational field, especially in the childhood age group. These deficiencies are evident both in the management of the theme in the daily school and in the education professionals' education. The intervention acted in order to ensure the role of teachers and, consequently, of the school institution, in preventive and protective action of integral development in childhood and in educational practices that operate from a perspective of diversity in education in sexuality and gender.